REFORMA AL CODIGO ORGANICO INTEGRAL PENAL, DEBE PERMITIRSE LA CONCILIACIÓN COMO MEDIOS ALTERNATIVOS DE SOLUCIÓN DE CONFLICTOS, EN EL PROCEDIMIENTO EXPEDITO DE CONTRAVENCIONES PENALES DE VIOLENCIA CONTRA LA MUJER Y MIEMBROS DEL NÚCLEO FAMILIAR - Troya Chicaiza, Jordan Miguel (2019)
The present legal research entitled "Reform of the Comprehensive Organic Criminal Code, allow reconciliation as an alternative means of resolving conflicts, in the expedited procedure of contraventions of violence against women and members of the nuclear family" determines that alternative means the solution of the conflicts is found in the constitutional norms and in the other cases the fulfillment of these matters is fulfilled in the contraventions of violence against the woman and the members of the nuclear family. In the present investigation it is verified that the application of the conciliation seeks to protect the rights, principles and constitutional guarantees of the family and of the people who are in the family environment. Clearly it has been proven that the Organic Comprehensive Penal Code in this class of offenses totally prohibits the conciliation, that is to say that the Judge can not pass to the parties a conciliation process, such is the case that there is the permissibility of this means of solution. of the Constitution of the Republic of Ecuador in relation to the family as the fundamental nucleus of society. The methodology applied to this legal research is the surveys and interviews, as well as the support of the bibliographic and documentary material, which served as the basis for proposing a reform to the Comprehensive Organic Criminal Code, in relation to conciliation in cases of Violence against women and members of the family, in order to protect and protect the principles, rights and constitutional guarantees in relation to the family such as the Constitution of the Republic of Ecuador. In addition to taking into account the protection of the rights of women and of those who are in the family environment, making 5 reference to the children we focus on that of the Republic of Ecuador also takes into account the Code of Children and Adolescence that seeks to guarantee the protection of rights. t should be emphasized that, in order to provide a better service as established by the Administration of Justice, the applicability of conciliation in matters of violence against women and family members is necessary, since through the use of this alternative means of conflict resolution we will guarantee the decision of the parties, in such a way that a personalized treatment can be given in each process and in which a specific solution to each case will be sought in order to seek the eradication of domestic violence. It is necessary to implement conciliation as a method of conflict resolution that acted neutrally and at the same time I sought to eliminate the problem that arises in each case such as violence against women and family members.